Construction of Enhanced Recovery Training Module for Former Drug Addicts - Mohd Hefzan, Azmi; Muhammad Nubli, Abdul Wahab (Penerbit UPSI, 2022)
Construction of an academic module requires few main objectives in the module construction which are Module Construction, Module Validity Assessment, Module Reliability Test, and Module Effectiveness on the Studied Variables Test. However, in this research, the researcher focuses on Module Construction, Module Validity and Module Reliability. In this research, Enhanced Recovery Training Module (ERTM) is implied to former drug addicts which refers to person under surveillance (PUS) as an extended training after being released from the rehabilitation center. PUS is those who has completed their treatment and rehabilitation program under Section 6(1)(a) [Magistrate's order to drug addicts to undergo treatment and rehabilitation at PUSPEN for a period of not more than 2 years and after that undergo supervision in the community for not less than 2 years]. The construction of activities in this module is based on the al-Ghazali counselling theory. The module construction in this research uses Sidek Module Construction Model and uses the descriptive research design to evaluate the validity of the module and to test the reliability of the module. To assess the validity of the module content, a total of nine experts in related fields have made a recommendation. Meanwhile, to assess the reliability, it involves 20 samples who had undergone a pilot test of the ERTM module and had answered the module reliability questionnaire. The findings show that Enhanced Recovery Training Module has achieved a high percentage of validity which is 90.3 percent and the high index value of content validity at 0.9. While the module reliability test using the Cronbach Alpha reliability coefficient is high which is .902. Therefore, this module is also able to provide new contributions to PUS as a follow-up training to help this target group continue to recover from addiction to illicit substances. It is hoped that the use of this module can also help reduce the risk of recurring addiction to the target group.